Network test starts in the lab. - Bretz, E.A.
The myriad elements of a multi-gigabit-speed optical-fiber network must be tested long before the network itself is field tested. By the time a component hits the field, it should only require a final functional test in the buyer's network. It should have gone through multiple simulations while in design, and several rounds of lab tests while in prototype stages, to ensure that it reliably handles gigabit data rates. The author describes the testing of components carried out by Williams Communications in its laboratories
Keywords: Williams Communications; Gigabit data rates handling; Laboratory tests; Multi-gigabit-speed optical-fiber network; Simulations